The Role of the Private Security Industry Regulation Authority (PSIRA) in Addressing Non-Compliance of Private Securities in Drinking Establishments in KwaZulu Natal, South Africa (London Journal of Research In Humanities and Social Sciences, 2023)
Some of the challenges facing the security service providers in South Africa have been met with policy measures to try to address it. For example, the Private Security Industry Regulation Authority (PSIRA) introduced the Private Security Industry Regulatory Amendment Bill to amend the PSIR Act to address the issues stemming from the changes and growth of the industry.  In addition, enforcement of the law and the prosecution of non-compliance within the industry has been in existence as a proactive measure to punish those security service providers who deliberately evade the statutory requirements. It still remains a concern for the researcher that with the effort put by PSIRA to enforce the statutory obligations across security service providers, minimal to none inspections are conducted in drinking establishments. Enforcement and inspection in the drinking establishments where security service providers are visible is important to ensure the behaviour and conduct is within the standards of the PSIR Act. This study investigates the effort put by PSIRA to enforce and ensure compliance of private securities in drinking establishments in KwaZulu Natal (KZN). By employing the qualitative research approach to the study, the study found that PSIRA is not efficient in monitoring and overseeing compliance of private securities in drinking establishments in KZN.
Keywords: text; cohesion; coherence; translation strategies; Personal autonomy. Children and adolescents. Patients. Informed Consent.; Private Security; compliance; enforcement; drinking establishments